Quantification of β-Elemene by GC–MS and Preliminary Evaluation of Its Relationship With Antitumor Efficacy in Cancer Patients - Juanjuan Hou; Jia Yi; Yan Wang; Lili Cui; Wenwen Xia; Zhengyan Liang; Liya Ye; Zhipeng Wang; Shouhong Gao; Zhan Wang (Journal of Analytical Methods in Chemistry)
Conclusions: This method was effectively developed, validated, and utilized to quantify β-elemene in cancer patients. The initial findings indicated no significant relationship between therapeutic efficacy and the concentration of β-elemene.